Assessing Knowledge and Practices of Farmers on Climate Change Adaptation in Panchkhal Municipality-3, Kavrepalanchok (Research Nepal Journal of Development Studies, 2025)
Climate change poses significant threats to agricultural sector in Nepal. This study assesses farmers' perceived knowledge on climate change in Panchkhal Municipality-3, focusing on effective climate change adaptations. The study used quantitative approach and survey method in which required data were collected from 108 farmers selected randomly. Primary data were collected through self-administered household survey questionnaires, while secondary data were generated from government reports and policy documents. The study used Integrated Farming Systems, and Cultural Theory of Risk for analyzing technological, ecological, and socio-institutional dimensions of adaptations. The study found that farmers are predominantly rely on digital platforms (42.6%) and traditional media (38%) for receiving climate change adaptations related information. Major threats of climate change include soil fertility loss (36.1%), erratic rainfall (21.3%), and high input costs (93.5%). While 75.9 percent of farmers reported experiencing extreme weather, adaptation practices remain limited, with only 29.6 percent adopting crop diversification and 21.3 percent dependent on chemical inputs. Institutional support is heavily state-centric, with 86.1 percent of farmers relying on government programs, yet coordination and resource allocation remain weak. The study concludes that despite awareness of climate risks, farmers' adaptive capacity is constrained by financial barriers, insufficient technical training, and ineffective governance. For applying effective adaptation strategies, national policy need to shift from a top-down approach to a subsidized, data-driven, and locally integrated approach. Municipal policy must prioritize hyper-local implementation through by-laws and municipal budgets that support capacity and skill development training, infrastructure upgrades, and institutional capacity of the stakeholders. Furthermore, market sector policy need to create an enabling environment through financial de-risking, standards for "climate-resilient" products, and Public Private Partnership frameworks. Agriculture cooperatives policy need to strengthen and empower farmers as central actors in adaptation.